EVALUASI PROGRAM PEMBELAJARAN LINK AND MATCH SMK DENGAN DUNIA USAHA/INDUSTRI - Dese, Aldo; Murwantini, Sri; Ratna Pancawati (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
This study aims to evaluate the Link and Match learning program in Light Vehicle Engineering at SMK Karsa Mulya Palangka Raya. The evaluation covers input and process aspects conducted by the school and the business/industry partner, namely PT. Murni Berlian Motor Palangka Raya (Mitsubishi Motors). Respondents included 30 students, 3 teachers/school administrators, and 3 representatives from the business/industry partner. Data were collected through surveys, interviews, and documentation, followed by descriptive analysis. The results show, first, that the implementation of the Link and Match program is considered good based on teacher readiness, teacher competence, student preparedness, facilities, and cooperation. The input evaluation falls into the good category, with an average score of 18.00. Second, the process of implementing this program in the business/industry sector is deemed good based on the facilities and infrastructure of the industry class, the role of teachers, the role of students, and work practices at the business/industry site, with an average score of 17.07 by students and 19.00 by teachers. To support and improve the quality of the Link and Match program, it is recommended to provide varied provision to enhance students' understanding of the material and to conduct in-depth evaluations of students' comprehension of vocational competences.